Dilema moral na Educação Infantil: generosidade ou justiça? - Kawashima, Rosana Akemi [UNESP] (2013)
The aim of this study is to investigate the judgments about the virtue of generosity or justice by teachers in early childhood education and compare their judgments with the children’s judgments about generosity or justice. We interviewed 26 teachers and 90 children aged 4, 5 and 6 years at this level of education. The instrument used was a moral dilemma in which the protagonist of the story would have to choose between giving a prize to the child who drew the most beautiful picture (justice) or to the child who was sad (generosity). The results indicate that justice is the virtue most valued by teachers and that it is already valued by children and may be a need for them. And generosity is valued more by children than by teachers.